Produtividade total dos fatores efetiva da indústria brasileira 1990-2009 - Luiz Dias Bahia (Instituto de Pesquisa Econômica Aplicada (IPEA), 2017)
– The main purpose of this paper is to calculate the effective total factor productivity (ETFP) of the Brazilian agricultural and industrial sectors during 1990-2009. The results are the following: all sectors have reached high ETFPs, with a few exceptions; however, the ETFPs have not mobilized many or all sectors of their supply chains. So the main policy recommendation is the development in Brazil of regulatory and contract legal rules that constitute actual and appropriate benchmarks.
Keywords: D2; D4; 330; effective total factor productivity; brazilian agriculture; brazilian manufacturing